Altered triglycerides and HDL-c are better marker for coronary heart disease in NIDDM - Ugle, Suresh Santu; Bikkad, Mahendra Dattatraya (International Journal of Research in Medical Sciences, 2016)
Background: Abnormalities that characterizes lipoprotein metabolism in non insulin dependent diabetes mellitus (NIDDM) patients, fasting concentration of triglycerde rich lipoprotein especially very low density lipoprotein (VLDL) are higher, and those of HDL, commonly measured as HDL-c, are lower than among people without diabetes, which leads to increased triglyceride HDL-c ratio and insulin resistance. This type of diabetic dyslipidaemia is major cause of endothelial damage and thus coronary heart disease (CHD). Methods: The study was carried at the Central Clinical Laboratory MIMSR Medical college Latur , NIDDM patient were selected after attending Medicine OPD MIMSR Medical college Latur, the lipid profile of 50 diabetic patients and 50 healthy subjects were determined and compared. Results: In the control group I mean values of total cholesterol were 175.55 ± 29.87 mg %, LDL-c 110.60 ± 28.73 mg % , serum triglycerides were 108.39 ± 39.62 mg %,HDL-c were 44.45 ± 6.7 mg% and In the group II serum triglycerides 145.68 ± 68.94 mg% and were significantly increased as compared to group I. The serum HDL-c group II 41.46 ± 6.6 mg % were significantly decreased as compared to group I (P is <0.05). Conclusions: A characteristic feature of NIDDM is the elevated triglycerides and lowered HDL-c levels, which leads to insulin resistance and CHD.